Synthesis of Benzopyran-Fused Flavone Derivatives via Microwave-Assisted Intramolecular C–H Activation - Sipos, Zoltán; Kónya, Krisztina (Synthesis, 2018)
A microwave-assisted intramolecular direct arylation method for the synthesis of benzopyran-fused flavone derivatives containing natural flavone backbones is described. Different polyalkoxy flavones were synthesized and functionalized with 2-bromobenzyl bromide. The resulting compounds were subjected to palladium-catalyzed intramolecular direct arylation reactions supported by microwave irradiation to produce fused tetracyclic flavones. In the case of the 7-substituted chrysin derivative, the regioselectivity of the coupling was also examined.
Keywords: flavones; C–H bond activation; palladium; intramolecular direct arylation; microwave chemistry